Efeito de cobertura antiaderente no acúmulo de biofilme em dispositivos ortodônticos - Oliveira, Adauê Siegert de (2012)
The use of orthodontic devices has been associated with an increase in dental biofilm retention. In this study, the effect of hydrophobic coatings, based on (fluorinated or not) organo-silanes, on the reduction of the contact angle and early biofilm retention in orthodontic devices was tested. Two different types of hydrophobic were tested: hydrophobic solution 1 (SH1), obtained by dilution of 2.5% of hexadecyl-triethoxy-silane in ethanol, and hydrophobic solution 2 (SH2), composed of 2.5% of perfluorodecyl-triethoxy-silane diluted in dimethyl sulfoxide. The solutions were applied in ceramic and stainless steel substrates and, via sol-gel process and crosslinking, siloxane networks were formed on the surface of the devices. The effect of the coatings was evaluated in two stages. In the first stage, aiming the characterization of the surface, the water contact angle was analyzed. Stainless steel and polycrystalline alumina plates were prepared, previously applying or not alumina sandblasting as surface treatment. A significant increase in contact angle was observed with the application of both hydrophobic solutions in both substrates, with the sandblasting allowing formation of super-hydrophobic surface in the ceramic substrate (contact angle up to 155o), while hydrophobic surfaces were obtained in the steel substrate (contact angle up to 123o). In the second phase, the effect of the hydrophobic coating on the biofilm retention in orthodontic brackets was evaluated using a microscosm model. Orthodontic brackets were previously prepared according to the surface treatments that showed the best results in the phase 1 (SH1 for steel, SH2 for ceramic). The effect of the coatings on the biofilm formation was evaluated in periods of 12h and 24h (controls: uncoated substrates and sandblasted substrates). The results showed that the hydrophobic coatings did not result in significant effect in biofilm retention for the time 12h, whereas all coating treatments significantly reduced the biofilm retention in the metal and ceramic brackets compared with the control groups. A significant exponential reduction in biofilm retention at 24h was associated with the increase in contact angle. It can be concluded that application of (super)-hydrophobic crosslinked coatings via sol-gel process on the surface of orthodontic metal and ceramic brackets reduced the surface wetting of the surfaces in contact with water and had a significant effect on the retention of dental biofilm after 24h